2021
DOI: 10.1051/ro/2020096
|View full text |Cite
|
Sign up to set email alerts
|

Research on manufacturer encroachment with advertising and design of incentive advertising: A game-theoretic approach

Abstract: This paper studies the advertising decision regarding a supply chain with manufacturer encroachment. It is assumed that the manufacturer and the retailer have different quantity decision power so as to explore how the first-mover advantage affect the advertising decision and the manufacturer encroachment. It is known that the manufacturer encroachment usually makes the retailer worse off. Our results show that (1) the retailer can benefit from encroachment when the manufacturer’s direct selling cost is high an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…Our work also relates to suppliers' encroachment in a supply chain (see, e.g., Liu and Zhang, 2006;Li et al, 2014Li et al, , 2015Chen, Ping et al, 2020;Ma, Junhai and Hong, Yalan, 2021). Arya et al (2007) showed that encroachment is beneficial to the retailer when no synergies are admitted by the supplier.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Our work also relates to suppliers' encroachment in a supply chain (see, e.g., Liu and Zhang, 2006;Li et al, 2014Li et al, , 2015Chen, Ping et al, 2020;Ma, Junhai and Hong, Yalan, 2021). Arya et al (2007) showed that encroachment is beneficial to the retailer when no synergies are admitted by the supplier.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Besides Arya's original work, Chiang et al (2003), Tsay and Agrawal (2009), and Cai (2010) also supported the “wholesale price effect.” They suggested that win–win situations could be achieved when the retailer had high marketing advantages. Zhang, Cao, and He (2020) and Ma and Hong (2021) found that manufacturer advertising contributed to the “demand expansion effect” that advertising effort was stepped up under encroachment and created more demand for the retailer. Ha et al (2016), Zhang et al (2019), and Shi (2019) found the “quality distortion effects” that the manufacturer either upward or downward distorted the product quality to mitigate demand cannibalization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are differences in the focus of research on manufacturer invasion, with some studies focusing on commodity brand effects, for example, manufacturer encroachment strategies under retailer store brands and national brands (Balasubramanian & Maruthasalam, 2021; Nie et al, 2021; Zhang, Liu, et al, 2021; Zhang, Song, et al, 2021) and private brand encroachment strategies (Li, Cai, & Chen, 2021; Li, Hu, et al, 2021; Li, Liang, et al, 2021). Manufacturer encroachment under advertising and marketing strategies (Huang et al, 2021; Ma & Hong, 2021; Zhang et al, 2019), green products and green investments (Li, Cai, & Chen, 2021; Li, Gong, et al, 2022; Li, Hu, et al, 2021; Li, Zhang, et al, 2022), manufacturer encroachment under information sharing (Huang, Chen, & Guan, 2020; Guo et al, 2023; Huang, Chen, & Xiao, 2020; Hu, Huang, et al, 2021; Hu, Sun, et al, 2021), and also some studies focus on manufacturer encroachment under information asymmetry (Gao et al, 2021; Xu & Xu, 2022). Also, Zhang et al (2022) explored the effect of supply chain channel structure on manufacturer encroachment decisions in a capital‐constrained or well‐capitalized state for retailers and found that the choice of trade credit financing by capital‐constrained retailers inhibits manufacturer encroachment.…”
Section: Literature Reviewmentioning
confidence: 99%